Pengaruh Waktu Dekomposisi dan Dosis Pupuk Kandang Kotoran Kambing Terhadap Pertumbuhan dan Hasil Tanaman Terong (Solanum melongena) - M. Iqbal Abdillah; Titin Setyorini; Pauliz Budi Hastuti (AGROISTA : Jurnal Agroteknologi, 2023)
The application of organic fertilizers in eggplant cultivation can reduce the use of chemical fertilizers which can damage the soil in long term. The maturity of organic fertilizer to be ready for application is highly dependent on the length of the decomposition process. This study aims to determine the effect of decomposition time and dosage of goat manure on the growth and yield of eggplant plants. The research was conducted from April to June 2022 in Maguwoharjo, Depok, Sleman, Yogyakarta. This study used a factorial experiment method arranged in a completely randomized design consisting of two factors. Factor I was decomposition time consisting of 3 levels, namely: 1 month (W1); 1,5 months (W2); 2 months (W3). Factor II was the dosage of goat manure consisting of 3 levels, namely, 100 g (D1), 200 g (D2), 300 g (D3). Each treatment was repeated 6 times. Data from the study were analyzed using variance analysis and continued with DMRT test at 5% significant level. The results showed no significant interaction between the treatment of decomposition time and dosage of goat manure on all parameters. Each treatment gave a different effect on the growth and yield of eggplant plants. The best decomposition time on the parameters of leaf area is 2 months, stem diameter is 1,5 months, and root length is 1 month. The best dosage of goat manure on leaf area parameter is 200 g, while on the number of leaves and number of flowers parameter is 300 g.